The Clinical Effect of Shirish Pushkaradi Yoga in the Management of Tamaka Shwasa – A Case Study - Rani, Simmi; Nagar, Rakesh Kumar; Kumar, Raj (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Bronchial Asthma (Tamak Shwasa) is the most common allergic disorder in the childhood and leading cause of hospitalization. It affects school attendance and school performance. It can also disrupts sleep, play and other activities, and growth of the child. It’s symptoms closely resemble with symptom of Tamaka Shwasa in Ayurveda which is due to disturbance in equilibrium of Kapha and Vata with Pitta Dosha, apart from Ama. According to the Ayurveda Chikitsa Siddhanta, it is explained that Virechana, Kapha-Vatahara drugs, and Vata-anulomana are the prime line of treatment in Tamaka Shwasa. Methods: This is a single case study, where in a 13-year-old female child, from rural area presented with the complaints of breathlessness and cough for 8 years of age and used antihistaminics and inhaler for relief. The symptoms aggravated with intake of cold food items - weather, relieved on medication. Respiratory examination revealed bilateral expiratory and inspiratory wheeze. The patient was prescribed capsule Shirish Pushkaradi Yoga with lukewarm water and was advised proper diet and regimen according to the disease and patient’s present conditions and the importance of Pathya in the case of Tamaka-Shwasa. Results: Significant amount of reduction in all the clinical signs and symptoms (cough, breathlessness quantity of sputum, difficulty in speech, body position, use of accessory muscles, respiratory rate, breath sound, and peak expiratory flow rate) was seen. Discussion: The ingredients of capsule Shirish-Pushkaradi Yoga have mainly Vata Kapha-hara action and thereby normalize the Gati of Vata Dosha by removing obstruction caused by Kapha.